CAREGIVER TRAINING ON CARE FOR PEOPLE WITH DEMENTIA IN MEDAN, NORTH SUMATERA - Siska Evi Martina (Faculty of Vocational Studies, Universitas Airlangga, 2020)
Background: Dementia is a syndrome due to brain disease, usually chronic or progressive and there is a dysfunction of noble function. The most common type of dementia is alzheimer’s dementia. Purpose: Improving the capability of caregiver for taking care people living with dementia. Method: The method used in this community engagement was coaching and training for caregivers who are generally families of the elderly with dementia. Caregiver is also taught about treatments and strategies that can be taken to meet the elderly’s daily needs. Demonstrations are also carried out on some care techniques for the elderly that are often not understood by caregiver. Result: The 15 participants who were present were all very active and enthusiastic involved during the activity. All participants were able to follow the activity well and gave many questions they had never known. Participants were able to demonstrate several techniques for treating people with dementia. The results of the questionnaire showed 100% of participants understood about dementia and dementia care. Conclusion: This activity could be regular program for improving capability of caregiver for taking care people living with dementia.